HUBUNGAN PENGETAHUAN IBU TENTANG KB JANGKA PANJANG DENGAN PEMILIHAN KONTRASEPSI JANGKA PANJANG - Pipin Rahmawati; Rosyidah Alfitri (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Introduction: This study examined how mothers' understanding of long-acting contraceptives influenced their choices. The study highlighted that limited awareness often leads to low adoption rates. By examining the relationship between maternal knowledge and contraceptive choice, this study aims to identify ways to improve education and increase the use of effective long-term family planning methods among women. Methods: This study used a cross-sectional design involving thirty new family planning acceptors. Data collection was done through a structured questionnaire, which allowed for a thorough understanding of the participants' perspectives. The data collected was analyzed using the Chi Square test to identify statistically significant relationships, which provided valuable information to inform future family planning initiatives. Results: The chi-square test showed a p value less than the significance level, indicating statistically significant results. Conclusion: Increased maternal knowledge will improve overall child health and well-being outcomes.